Testing the sources of the peculiar abundances in globular clusters - Vaca, Ricardo J.; Cabrera-Ziri, Ivan; Magris, G. C.; Bastian, N.; Salaris, M. (Astronomy and astrophysics, 2024)
This work aims to analyze some of the polluters proposed in the self-enrichment scenarios put forward to explain the multiple populations in globular clusters (GCs), extending previous studies. Three scenarios with different polluter stars were tested: asymptotic giant branch stars (AGBs), high-mass interacting binaries (IBs), and fast rotating massive stars (FRMSs). With abundance data available from the Apache Point Observatory Galactic Evolution Experiment (APOGEE) survey and ΔY estimates from precise Hubble Space Telescope (HST) photometry, twenty-six clusters were studied, increasing the number of clusters in previous studies by more than a factor of three. We also included the study of the abundances of N, C, Mg, and Al, extending previous studies that mainly focused on the abundances of He, O, and Na. In addition, we constructed an empirical model to test whether one could explain the chemical signatures of the “enriched” population of GC stars with a fixed source and dilution process based on empirical data. In agreement with work by other authors, we found that the proposed polluters can generally predict the qualitative abundance patterns in GC stars and in some cases quantitatively predict some elements, but in most cases when we compare the model yields with the observations, we find that they cannot explain the entire set of observed abundance patterns. The empirical model succeeds in reproducing the abundances of Al for a given ΔY (and vice versa), showing that there is a direct relationship between Al and He, with one increasing proportionally to the other. However, the empirical model fails to reproduce the observed abundances of Na and N, in agreement with the results of previous works. The observed decoupling between the maximum abundances of CNO-cycle elements such as N and Na with those of Al and He provides new information and constraints for future models and could take us a step closer to understanding the origin of the peculiar abundance variations of GC stars.
Online erschienen: 08. Oktober 2024
Gesehen am 04.06.2025